Efektifitas Daun Sembung (Blumea balsamifera) Sebagai Feed Aditif Bagi Ternak: Effectiveness of Sembung Leaf (Blumea balsamifera) as a Feed Additive for Livestock - Amriana Hifizah; Yurio Yusuf; Anas Qurniawan; Astati Astati (Universitas Islam Negeri Alauddin Makassar, 2023)
Blumea balsamifera (sembung) is a type of herbal plant that grows wild and has a bioactivity function for livestock. This study aims to find out how the effect of adding sembung leaf flour (Blumea balsamifera) has on the performance and digestive profile of broiler organs. This study was designed using a completely randomized design (CRD) with 4 treatments and 3 replications for each treatment, where the treatments were: P0 (Control); P1 (Commercial Feed + 3% Sembung flour); P2 (Commercial Feed + 4% Sembung flour); P3 (Commercial Feed + 5% sembung flour). The parameters observed in this study were performance which included feed consumption, body weight gain (PBB), feed conversion ratio (FCR) and profile which included the proportion of weight and length of digestive organs. Processed data were analyzed using analysis of variance from RAL and continued with Duncan's test if the results were significant. The B.balsamifera supplementation treatment at the 3% level indicated better body weight gain and ration conversion compared to other treatments. Giving B. balsamifera to a level of 5% in broiler feed does not have an adverse effect on broiler performance and the profile of their digestive organs.